DNA repair polymorphisms and cancer risk in non-smokers in a cohort study. - Matullo, G; Dunning, A; Guarrera, S; Baynes, C; Polidoro, S; Garte, S; Autrup, H; Malaveille, C; Peluso, M; Airoldi, L; Veglia, F; Gormally, E; et al. (2006)
Environmental carcinogens contained in air pollution, such as polycyclic aromatic hydrocarbons, aromatic amines or N-nitroso compounds, predominantly form DNA adducts but can also generate interstrand cross-links and reactive oxygen species. If unrepaired, such lesions increase the risk of somatic mutations and cancer. Our study investigated the relationships between 22 polymorphisms (and their haplotypes) in 16 DNA repair genes belonging to different repair pathways in 1094 controls and 567 cancer cases (bladder cancer, 131; lung cancer, 134; oral-pharyngeal cancer, 41; laryngeal cancer, 47; leukaemia, 179; death from emphysema and chronic obstructive pulmonary disease, 84). The design was a case-control study nested within a prospective investigation. Among the many comparisons, few polymorphisms were associated with the diseases at the univariate analysis: XRCC1-399 Gln/Gln variant homozygotes [odds ratios (OR) = 2.20, 95% confidence intervals (CI) = 1.16-4.17] and XRCC3-241 Met/Met homozygotes (OR = 0.51, 95% CI = 0.27-0.96) and leukaemia. The recessive model in the stepwise multivariate analysis revealed a possible protective effect of XRCC1-399Gln/Gln in lung cancer (OR = 0.22, 95% CI = 0.05-0.98), and confirmed an opposite effect (OR = 2.47, 95% CI = 1.02-6.02) in the leukaemia group. Our results also suggest that the XPD/ERCC1-GAT haplotype may modulate leukaemia (OR = 1.28, 95% CI = 1.02-1.61), bladder cancer (OR = 1.38, 95% CI = 1.06-1.79) and possibly other cancer risks. Further investigations of the combined effects of polymorphisms within these DNA repair genes, smoking and other risk factors may help to clarify the influence of genetic variation in the carcinogenic process.